Plate IX: Invertebrates including comatula, sea urchin, starfish and sea cucumber - Haeckel, Ernst (Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, 1872)
Plate depicts several invertebrates including a starfish (figure A. Uraster), a Comatula (figure B), a sea urchin (figure C echinus), and a sea cucumber (figure D Synapta). Haeckel is known for his descriptive work on marine organisms including radiolarians, poriferans (sponges), and cnidarians (jellyfish, anemones and corals). This plate can be found in Ernst Haeckel's Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, or The History of Creation: Or the Development of the Earth and Its Inhabitants by the Action of Natural Causes.
Keywords: Evolution; Heredity; Invertebrates; Cnidaria; Sea cucumbers; Starfishes; Sea anemones